Genetic factors in the development of pulmonary embolism - N. M. Kryuchkova; A. A. Chernova; S. Yu. Nikulina; V. N. Maksimov (Российский кардиологический журнал)
The article presents a literature review on the study of the relationship of FGA, FGB, F2, F5, PAI, ITGA2 gene polymorphisms with the development of pulmonary embolism (PE). We concluded that genetic factors in the development of PE are to a greater extent mutations in the F2, F5, PAI, ITGA2 genes. There is a positive correlation between the presence of combined genetic mutations and the development of PE. The study of allelic polymorphism of hemostasis genes makes it possible to predict coagulation system disorders, including PE.